Las perspectivas eclesiológicas del papa Francisco según la Fratelli tutti (2021)
Since his election in 2013, Papa Francisco has surprised the world with his spontaneity, words and gestures. He has renounced ostentatious dress, is interested in the poor, the marginalized, the excluded, and wishes to renew the Ecclesial Institution. His first speeches focused on the concept of mercy to the point that he called for an extraordinary Jubilee, recalling that being merciful is the principal vocation of every missionary disciple of Jesus. Papa Bergoglio is clear that the Church must be open to renewal, to change and as a result of this ecclesial desire is the Encyclical Letter Fratelli Tutti, published on 3 October 2020. In this document we do not find issues of a theological, dogmatic, canonical or sacramental nature. The Pope does not say anything about synodality, nor does he denounce sins of sexual morality, nor does he stop at details of how to receive Eucharistic communion. That wasn’t his style. What the Supreme Pontiff desires and expects of the Catholic Church is that it should come out of its confinement and false assurances, that it should not pass by, ignore, or disengage from others. Rather, may he be at the service of fraternity and social friendship.